PENGARUH DOSIS PUPUK ORGANIK LIMBAH KULIT KOPI DAN KONSENTRASI CUKA KAYU (Wood Vinergar) KINA (Chinchona spp) TERHADAP PERTUMBUHAN BENIH KOPI DI PERSEMAIAN - Vera Purnama dan Lusiana (Program Studi Agroteknologi Faperta UNIBBA, 2022)
This study aims to determine: The effect of the interaction of organic fertilizer dose of coffee husk waste and quinine wood vinegar concentration on the growth of coffee seeds in nurseries. The research was carried out on the land of the Faculty of Agribusiness and Agricultural Engineering, Subang University, West Java Province with an altitude of 118 meters above sea level with an average temperature of 28 – 30 C, the experiment was carried out from May to July 2019, the type of rainfall was very wet. The method used in this study is an experimental method with a Randomized Block Design with a factorial pattern consisting of 2 treatment factors. The first factor is the dose of coffee husk waste (P) consisting of 4 treatment levels, namely p0 = 0 t ha-1 organic fertilizer for coffee husk waste; p1 = 5 t ha-1 organic fertilizer from coffee husk waste; p2 = 10 t ha-1 organic fertilizer from coffee husk waste; p3 = 15 t ha-1 organic fertilizer from coffee husk waste. The second factor is the concentration of quinine vinegar (C) which consists of 4 levels of treatment, namely c0 = 0% quinine vinegar; c1 = 1% quinine vinegar; c2 = 2% quinine vinegar; and c3 = 3% quinine vinegar. The results showed that for the treatment of organic fertilizer coffee husk waste at 6 WAP and 8 WAP there was an increase in growth at a dose of 5 t ha. Wood vinegar concentration of 3% gave significant growth at 6 WAP observations and the best results. There was no interaction between the use of organic fertilizer dose of coffee husk waste and quinine wood vinegar concentration on the growth of coffee seeds in the nursery.